Trade with the EU, Variable Geometry and Human Rights in the EAC (Milan Law Review, 2022)
The Economic Partnership Agreement between the East African Community (EAC) and the European Union (EU) is of particular importance for the Kenyan floriculture sector. While the other EAC Partner States remain reluctant to ratify this agreement, they allowed the Republic of Kenya to start its implementation under the principle of variable geometry in June 2021. Kenya and the EU then started a strategic dialogue in which they pledged to strengthen their cooperation on human rights issues. This article identifies two priorities for floriculture workers: Kenya’s ratification of the core labour rights Convention No. 87 on the Freedom of Association and Protection of the Right to Organise and the broadening of an enabling space for an active, organised and transparent civil society.
Keywords: Kenya; Freedom of Association; Flowers; COTU-K; post-Cotonou